TINDAK TUTUR DAN KESANTUNAN DALAM BAHASA MELAYU LANGKAT - T. Syarfina (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Language is a tool that plays a role in human life to declare or express feelings, the events that are experienced by individuals and shared by a set of language users. Discuss regional languages still play an important role in the life of Indonesian people. It is clearly seen that most of Indonesian speakers still use the local language or local language as a mother tongue. Language areas, in particular have accrued as a mother tongue, and has a function as a symbol of regional identity, means of transportation or communication in daily activities, both within and between groups keluaraga speakers of that language. This study talked about speech acts and politeness Malay Langkat. The problem is studied in terms of speech acts, kesatunan tactics, and typology of politeness.